A Cataract Surgery Barrier Model In Eastern Zone Of Peninsular Malaysia - Abdul Mutalib, Othman; Asma', Hassan; Nurulain, Mat Zin; Ahmad, Shahir (2018)
Cataract is a serious public health problem as it is the most common cause of blindness in Malaysia and globally. Timely cataract surgery is required to prevent visual loss. This model illustrates the barriers in accessing cataract surgery services in the eastern zone of Peninsular Malaysia. Factors identified are personal issues, followed by issues at the primary care and specialist care level. This model is designed to elucidate the effect of delayed presentation, detection, and referral procedure for the provision eye care and cataract surgery to prevent blindness required to maintain the best quality of life and wellbeing.